Adjuvant leuprolide with or without docetaxel in patients with high‐risk prostate cancer after radical prostatectomy (TAX‐3501): Important lessons for future trials. Issue 20 (13th August 2013) - Schweizer, Michael T.; Huang, Peng; Kattan, Michael W.; Kibel, Adam S.; de Wit, Ronald; Sternberg, Cora N.; Epstein, Jonathan I.; Eisenberger, Mario A.
Abstract : BACKGROUND: The current trial evaluated 2 common therapies for patients with advanced prostate cancer, docetaxel and hormonal therapy (HT), in the surgical adjuvant setting. METHODS: TAX‐3501 was a randomized, phase 3, adjuvant study post‐radical prostatectomy (RP) in high‐risk patients with prostate cancer (n = 228) comparing 18 months of HT with (CHT) without docetaxel chemotherapy either immediately (I) or deferred (D). High‐risk disease was defined as a 5‐year freedom‐from‐disease‐progression rate of ≤ 60% as predicted by a post‐RP nomogram. Progression‐free survival (PFS), including prostate‐specific antigen disease recurrence, was the primary endpoint. The authors also assessed the accuracy of the nomogram and analyzed testosterone recovery in 108 patients treated with HT who had at least 1 posttreatment testosterone value. RESULTS: Between December 2005 and September 2007, 228 patients were randomized between the treatment cohorts. TAX‐3501 was terminated prematurely because of enrollment challenges, leaving it underpowered to detect differences in PFS. After a median follow‐up of 3.4 years (interquartile range, 2.3‐3.8 years), 39 of 228 patients (17%) demonstrated PSA disease progression, and metastatic disease progression occurred in 1 patient. The median time to baseline testosterone recovery after the completion of treatment was prolonged at 487 days (95% confidence interval, 457‐546 days). The nomogram's predicted versus observed freedom from disease progression was significantly different for the combination D(HT) and D(CHT) group ( P  < .00001). CONCLUSIONS: TAX‐3501 illustrated several difficulties involved in conducting postoperative adjuvant systemic trials in men with high‐risk prostate cancer: the lack of consensus regarding patient selection and treatment, the need for long follow‐up time, nonvalidated intermediate endpoints, evolving standard approaches, and the need for long‐term research support. Except for selected patients at very high‐risk of disease recurrence and death, surgical adjuvant trials in patients with prostate cancer may not be feasible. Cancer 2013;119:3610–3618 . © 2013 American Cancer Society. Abstract : The role of adjuvant systemic therapy after radical prostatectomy in patients with prostate cancer remains unclear. Trials in these patients are difficult for a multitude of reasons.